Anotações Semânticas em Repositórios Acadêmicos: Um estudo de caso com o RI UFBA - Rocha, Aline Meira; Salvador, Lais do Nascimento; Souza, Marlo V. dos Santos e (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
The current Web is syntactic and it is impossible for machines to process it. The Semantic Web with its technologies can bring more meaning to web content. UFBA’s IR is on the Syntactic Web and the recovery of deposited items isn’t always done efficiently. Information about the deposited items is stored in their metadata, but it is done manually and, not always, the chosen terms are able to help with the description process. The automatic semantic annotation method would certainly help librarians during the validation of the production’s deposit as well as enabling the recovery of UFBA’s IR items. The main proposal is to create a solution to semantically annotate the academic repository items in a semi-automatic method so to extract relevant terms that will be suggested to annotate the UFBA’s IR items making it a semantic repository.